2014
DOI: 10.1007/s12032-014-0966-8
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Dickkopf-1 predicts poor prognosis for patients with hepatocellular carcinoma after orthotopic liver transplantation by promoting cancer metastasis and recurrence

Abstract: Our previous data had shown that Dickkopf-1 (DKK1) combined with β-catenin was a novel prognostic predictor for hepatocellular carcinoma (HCC) patients. However, the role and mechanism of DKK1 in HCC recurrence or metastasis remain poorly understand. This study was to assess the role of DKK1 in tumor metastasis for patients with hepatocellular carcinoma after orthotopic liver transplantation (OLT). The expression of DKK1 protein was detected in hepatic cell lines, HCC cell lines, and HCC patients after OLT wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…In both breast cancer and hepatocellular carcinoma xenograft models, DKK1 increased tumour growth and promoted angiogenesis, suggesting that DKK1 has pro‐angiogenic activity (Smadja et al , ; Tung et al , ). In support of this, knockdown of DKK1 decreased tumour growth and angiogenesis in hepatocellular carcinoma (Huang et al , ). In addition to affecting primary tumour growth, DKK1 has also been linked to the development of metastasis in bone, breast, liver, lung and prostate cancer models, possibly related to the prominent role of DKK1 in stimulating migration and invasion observed in vitro (Thudi et al , ; Tao et al , ; Huang et al , ; Goldstein et al , ; Malladi et al , ; Pang et al , ).…”
Section: Dkk1 Promotes Proliferation Invasion and Tumour Growth In Pmentioning
confidence: 79%
“…In both breast cancer and hepatocellular carcinoma xenograft models, DKK1 increased tumour growth and promoted angiogenesis, suggesting that DKK1 has pro‐angiogenic activity (Smadja et al , ; Tung et al , ). In support of this, knockdown of DKK1 decreased tumour growth and angiogenesis in hepatocellular carcinoma (Huang et al , ). In addition to affecting primary tumour growth, DKK1 has also been linked to the development of metastasis in bone, breast, liver, lung and prostate cancer models, possibly related to the prominent role of DKK1 in stimulating migration and invasion observed in vitro (Thudi et al , ; Tao et al , ; Huang et al , ; Goldstein et al , ; Malladi et al , ; Pang et al , ).…”
Section: Dkk1 Promotes Proliferation Invasion and Tumour Growth In Pmentioning
confidence: 79%
“…Recently, a modification of this model, the BALAD-2 score, was validated in an international setting and confirmed to reliably predict the prognosis of patients with HCC [81] . Other circulating biomarkers that mirror current knowledge on pathways involved in hepatocarcinogenesis and shown to be of prognostic value are, amongst others, IGF1 [82] , DKK1 [83,84] , GPC-3 and HSP 70 [85] although prospective validation studies are still to come. In patients with advanced HCC, baseline angiopoietin 2 (Ang2), and VEGF concentration in the plasma also independently predict survival [76] .…”
Section: Non-invasive Prognostic Biomarkers In Hccmentioning
confidence: 99%
“…Therefore, we can foresee that HCC patients with high levels of preoperative serum DKK1 or both DKK1 and AFP may have poor prognosis after tumor resection, and then an adjuvant effective treatment should be considered. Previously, we demonstrated by tissue microarray that DKK1 could predict prognosis for HCC patients after tumor resection or orthotopic liver transplantation [25,26]. A recent metaanalysis concluded that DKK1 might be a novel common prognostic marker for human tumors, though most of these studies involved for analysis were based on immunohistochemistry results [27].…”
Section: Months After Operation (M)mentioning
confidence: 99%
“…Of interest, a recent study reported that ectopic expression of DKK1 could stimulate β-catenin expression [38]. DKK1 was also found to be preferentially expressed in metastatic HCC cell lines and HCC patients with recurrence, and could promote migration and invasion in vivo and in vitro through RhoA and JNK or MMP7 [25][26][38][39]. Nevertheless, more mechanisms of DKK1 in HCC still need to be further investigated.…”
Section: Months After Operation (M)mentioning
confidence: 99%